Simplification of Law Regulations in Copyright Criminal Act Settlement - Soeleman Djaiz Baranyanan (Lembaga Contrarius Indonesia, 2021)
The existence of overlapping laws and regulations in the Intellectual Property Rights (IPR) sector creates conflicts in their implementation. For example, the obligation to mediate as a condition for carrying out criminal charges for copyright infringement is based on Article 95 paragraph (4) of Law Number 28 of 2014 concerning Copyright. Mediation provisions in Law Number 30 of 1999 concerning Arbitration are a way of settling civil disputes outside the court to settle by deliberation and consensus with the help of a mediator. Meanwhile, mediation based on Perma Number 1 of 2008 is intended as an obligation for judges at the first level court in the District Court and Religious Courts in the context of resolving civil disputes. Settlement of copyright disputes is the authority of the Commercial Court, as a special court within the general court environment. However, the Commercial Court does not apply the obligation of mediation. The study results indicate that the simplification of legislation in the intellectual property sector will result in quality, simple, orderly legislation that will also increase investment, create employment opportunities, reduce the burden on society and the efficiency of the state budget.Keywords: Simplification; Copyright; Criminal Act Settlement